A shift in values is needed to address climate change impacts affecting communities and the environment in the Philippines - Ma. Isabel D. Dalhog (Davao Research Journal)
This feature essay explores the intricate symbiotic link that exists between human values and the planet's resources. It emphasizes the crucial relationship between human survival, economic growth, and environmental preservation. The Philippines, a country blessed with immense biodiversity, is highly reliant on natural resources for subsistence, livelihood, and well-being. The Philippines is at serious ecological risk due to unsustainable practices, particularly in the field of marine ecology. The growing threat of climate change only serves to intensify this approaching ecological disaster. The weight of addressing these challenges ultimately falls upon the shoulders of the youth, who will bear the consequences of the acts of the current generation. The paper highlights the importance of human activity in causing climate change impacts and emphasizes the urgent necessity for societal values to change in order to prevent looming environmental crises. It issues a compelling call to action, urging individuals and society as a whole to recognize their shared responsibility in minimizing the adverse impacts of climate change. Educational institutions stand out as significant catalysts for change, boosting environmental awareness and developing sustainable behaviors. The essay highlights the moral and just aspects of climate responsibility and the need for governments to take preventive action. The essay concludes that there is a need for collaborative, united efforts in the Philippines to safeguard and conserve the environment as a crucial prerequisite for a sustainable future to mitigate climate change impacts.